Peningkatan Produktivitas Masyarakat Melalui Teknologi Tepat Guna Bagi Peningkatan Ekonomi Masyarakat Berdasarkan Kearifan Budaya Lokal Di Desa Kadubereum Kecamatan Padarincang - Erni Krisnaningsih (Lembaga Pengembangan, Penelitian dan Pengabdian Kepada Masyarakat Universitas Banten Jaya, 2019)
Improving the standard of living is one of the most important factors in community survival. This must continue to be supported along with developments and competitiveness in the current era of globalization. Based on the results of mapping / assessment, it is known that Kadubereum Village has abundant natural potential, but it has not been supported by skilled human resources, especially in terms of traditional food processing, natural tourism management, and delivery of information through internet media. So that the living conditions of the community, especially in the economic aspects are not yet adequate, this is caused by several factors such as the still poor quality of human resources and inadequate village infrastructure. The main objective in this service activity is to provide Training and Counseling to the people of Kadubereum Village. What is done both in theory and practice in an effort to Improve Community Economy Through activities to increase community productivity through appropriate technology for improving the community's economy based on local cultural wisdom. With this kind of activity, it is expected to improve the economy and stimulate the creation of innovation and creativity to create superior local products and the development of natural attractions.